2018
DOI: 10.1111/raq.12254
|View full text |Cite
|
Sign up to set email alerts
|

Tilapia lake virus: a threat to the global tilapia industry?

Abstract: Tilapia lake virus (TiLV) is a recently described virus affecting wild and farmed tilapines. At present, it has been reported on three continents (Asia, Africa and South America) and the number of countries where the agent has been detected is likely to increase rapidly as a result of increased awareness, surveillance and availability of diagnostic methods. Any lack of openness regarding the TiLV status of a translocating live tilapia population destined for aquaculture may inadvertently contribute to the spre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
138
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(155 citation statements)
references
References 43 publications
3
138
0
3
Order By: Relevance
“…The aetiological agent(s) of the remainder of the TSC were not clear. TSC may be associated with a single or multiple factors known to cause tilapia mortality, such as streptococcal infections or external parasite infestations (Jansen et al, ). In this study, bacteriological testing and parasitological testing were not performed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiological agent(s) of the remainder of the TSC were not clear. TSC may be associated with a single or multiple factors known to cause tilapia mortality, such as streptococcal infections or external parasite infestations (Jansen et al, ). In this study, bacteriological testing and parasitological testing were not performed.…”
Section: Resultsmentioning
confidence: 99%
“…Tilapia lake virus (TiLV) is an emerging viral disease that affects several tilapia species in different countries on four continents: Asia, Africa, South and North America (Jansen, Dong, & Mohan, ; OIE, ). The virus was first described in Ecuador, affecting Nile tilapia ( Oreochromis niloticus ) fingerlings; it was diagnosed by histopathology and transmission electron microscopy and termed syncytial hepatitis of farmed tilapia (Ferguson et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Tilapia lake virus, a recently identified pathogen, firstly discovered in Israel (Eyngor et al, ), nowadays is being found in Asia, Africa and South America (Jansen, Dong, & Mohan, ), causes recurrent outbreaks in both wild and cultured tilapia (Ferguson et al, ). These outbreaks are characterized by significant mortality and morbidity, resulting in massive losses to tilapia industry (Tattiyapong et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tilapia lake virus (TiLV) is an emergent orthomyxo ‐like virus with negative sense RNA genome affecting tilapines and a few other cultured species of fish including giant gourami ( Osphronemus goramy ) (Jaemwimol et al, ; Tattiyapong, Dachavichitlead, & Surachetpong, ). Since first suspected cases emerged in tilapia in 2009 (Eyngor et al, ), outbreaks of the disease have been confirmed in at least 10 countries on four different continents (Asia, Africa, North America and South America) with evidence of continuous expansion (Eyngor et al, ; Jansen, Dong, & Mohan, ; OIE, ). TiLV infections are typically associated with high mortality, up to 90% in most cases (Dong et al, ; Surachetpong et al, ) and up to 100% in experimental trials (Behera et al, ), which emphasizes its threatens to the tilapia aquaculture industry worldwide.…”
Section: Introductionmentioning
confidence: 99%